Ranking of meal preferences and interactions with demographic characteristics: a discrete choice experiment in young adults - Katherine M. Livingstone; Karen E. Lamb; Gavin Abbott; Tony Worsley; Sarah A. McNaughton (BMC, 2020)
Abstract Background The diet of young adults is poor, yet little is known about the relative importance of influences on healthy eating in a decision-making context. The aim of this exploratory study was to understand the relative ranking of influences on meal choices in young adults and to investigate interactions between meal preferences and demographic and health characteristics. Methods Adults aged 18-30 years (n = 92, mean age: 23.9 (SD 3.4) years) completed an online discrete choice experiment. Participants were presented with 12 choice sets reflecting a typical weekday meal and were asked to choose between four meal options. Each meal consisted of a combination of five meal attributes (preparation time, cost, taste, familiarity and nutrition content) that each had three attribute levels. Data were analysed using conditional logit models. Subgroup analyses were performed by sex, education, income, weight status and meeting fruit and vegetable recommendations. Results Comparing the highest and lowest attribute levels, meal preferences were higher for better taste (B = 0.38; 95% CI: 0.12, 0.63), familiarity (B = 0.37; 95% CI: 0.21, 0.54) and nutrition content (B = 1.11; 95% CI: 0.81, 1.41) and lower for increased preparation times (B = −0.33; 95% CI: − 0.53, − 0.12) and cost (B = −0.50; 95% CI: − 0.75, − 0.24). Nutrition content was the most important influence on meal choice. Cost was the second most important, followed by taste, familiarity and preparation time. Compared to males, females had a higher preference for better nutrition content, taste and familiarity and a lower preference for increased cost. Higher educated participants had a higher preference for better nutrition content, familiarity and taste compared to lower educated participants. Young adults who met recommendations for fruit and vegetable intake had a higher preference for better nutrition content compared to participants who did not meet recommendations. Conclusion Nutrition content was the most important influence on young adults' meal choices, followed by cost, taste, familiarity and preparation time. Preferences varied by demographics and health characteristics, suggesting that the focus of dietary interventions may benefit from being tailored to specific young adult groups.